Phonological awareness, verbal working memory and rapid automatic naming as indicators of vocabulary development in preschool children - Ječmenica, Nevena; Golubović, Slavica (Specijalna edukacija i rehabilitacija, 2021)
Introduction. According to the lexical restructuring model, the development of vocabulary initiates the development of phonological representations. Therefore, it can be predicted that children with developed vocabulary will possess very specific phonological representations of words. Aim. The aim of this research was to determine the significance of phonological awareness, verbal working memory, and rapid automatic naming as indicators of the development of expressive and receptive vocabulary in preschool children. Method. The research included 86 children of typical development. For the assessment of phonological awareness, verbal working memory, rapid automatic naming, expressive and receptive vocabulary, the subtests of Clinical Evaluation of Language Fundamentals – Fourth Edition battery were used. Results. The results showed that the model containing age, phonological awareness, verbal working memory, and rapid automatic naming predicted 51% of the achievement variance on expressive vocabulary tasks (F = 7.73, df1 = 2, df2 = 75, p < .001) and 38% of the achievement variance on receptive vocabulary tasks (F = 4.65, df1 = 2, df2 = 75, p < .001). In the final model, only the tasks of phoneme identification, phoneme substitution, and rapid automatic naming (p < .05) stood out as statistically significant indicators of expressive vocabulary. On the other hand, statistically significant indicators of receptive vocabulary included analysis and synthesis of phonemes, verbal working memory, and rapid automatic naming (p < .05). Conclusion. The results showed that age, phonological awareness, verbal working memory, and rapid automatic naming significantly contributed to vocabulary development in children before reading acquisition.